Persepsi Mahasiswa Magister Universitas Islam Negeri Sumatera Utara Dalam Pemanfaatan Database Jurnal Cambridge - Shinta Dewi; Retno Sayekti; Franindya Purwaningtyas (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
This study aims to find out how the perceptions of master students at the State Islamic University of North Sumatra in terms of knowledge and experience in utilizing the Cambridge journal database. The research method used was qualitative with the informant selection technique using snowball sampling and five informants were obtained who knew and had accessed the Cambridge database. Data collection techniques used observation, interviews, and documentation. The research results showed that the majority of informants did not know that the UINSU Library had subscribed to the Cambridge journal database service. Most students know about the database of Cambridge journals obtained from outsiders when they were undergraduate students so that it has an impact on usage statistics with 104 downloads per year. This is caused by promotions related to journal services that are not carried out evenly throughout the academic community due to the difference in location between the library and the postgraduate campus. There are several factors inhibiting students from not using the Cambridge journal database such as access to closed articles which causes students not to use the campus network to open access automatically or not to use accounts and passwords provided to log in outside the campus network.